2018
DOI: 10.1002/art.40456
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Proteasomal Function in Human Osteoarthritic Chondrocytes Can Contribute to Decreased Levels of SOX9 and Aggrecan

Abstract: Objective Osteoarthritis (OA) chondrocytes have impaired autophagy, one arm of the proteostasis network that coordinates proteome and organelle quality control and degradation. Deficient proteostasis impacts differentiation and viability, and inflammatory processes in aging and disease. Studying OA chondrocytes, we assessed ubiquitin proteasome system proteasomal function. Methods We evaluated human knee cartilages by immunohistochemistry, and assessed proteasomal function, levels of proteasomal core subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Collagen type II (COL2A1), as a downstream target protein Sox9, is an important component of the cartilage matrix and is thought to be the basis of structural strength against outside pressure 40 . Similarly, aggrecan (Acan) is one of the main components of the ECM of articular cartilage and is necessary to maintain the normal shape of cartilage tissue 41 . In our study, we found that, compared with the levels in the BMSCs, the expression levels of COL2A1 and Acan were higher in the pBMSCs 14 days after chondrogenic differentiation, findings that confirm the predominance of the chondrogenic differentiation ability of pBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen type II (COL2A1), as a downstream target protein Sox9, is an important component of the cartilage matrix and is thought to be the basis of structural strength against outside pressure 40 . Similarly, aggrecan (Acan) is one of the main components of the ECM of articular cartilage and is necessary to maintain the normal shape of cartilage tissue 41 . In our study, we found that, compared with the levels in the BMSCs, the expression levels of COL2A1 and Acan were higher in the pBMSCs 14 days after chondrogenic differentiation, findings that confirm the predominance of the chondrogenic differentiation ability of pBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is suggested that proteasome ubiquitination plays a role in arthritis diseases. 28 Proteasome inhibitor MG132 29 or Ub K48R mutation 30 protected the cartilage from cytokine-mediated degradation and against DMM-induced OA in mice. FBXO6, one of the five F-box proteins predicted to bind glycoprotein substrates through FBA domain, is shown to bind high mannose N-linked glycoproteins and functions as ubiquitin ligase subunits.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complexity inherent in these responses, which resulted from identification of the numerous miRs involved in the pathogenesis and progression of human OA, created uncertainty as to how employing exogenous miRs could alter articular cartilage ECM aberrant turnover and ECM degradation, all of which are consistent characteristics of OA progression to joint failure. Perhaps more germane to their potential as translational medicines is that miRs were employed to identify additional targets for intervention in OA, including those involved in autophagy and proteasome-mediated protein degradation [ 89 ]. Furthermore, results of experimental studies performed in well-validated animal models of OA in which miRs were administered to these animals confirmed that miRs were active in vivo T .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%